2012
DOI: 10.1371/journal.pone.0044220
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights into the Echinoderm Nervous System from Histaminergic and FMRFaminergic-Like Cells in the Sea Cucumber Leptosynapta clarki

Abstract: Understanding of the echinoderm nervous system is limited due to its distinct organization in comparison to other animal phyla and by the difficulty in accessing it. The transparent and accessible, apodid sea cucumber Leptosynapta clarki provides novel opportunities for detailed characterization of echinoderm neural systems. The present study used immunohistochemistry against FMRFamide and histamine to describe the neural organization in juvenile and adult sea cucumbers. Histaminergic- and FMRFaminergic-like i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 54 publications
0
30
0
Order By: Relevance
“…A recent report characterizing the distribution of FMRFamide- and histamine-like immunoreactivities in the nervous system of L. clarki (Hoekstra et al 2012) provides for a comparison of the results obtained in this species with our three novel markers. In general terms, the immunoreactivity of all the antibodies is found within the same structures, in small subset of cells and fibers.…”
Section: Discussionmentioning
confidence: 98%
“…A recent report characterizing the distribution of FMRFamide- and histamine-like immunoreactivities in the nervous system of L. clarki (Hoekstra et al 2012) provides for a comparison of the results obtained in this species with our three novel markers. In general terms, the immunoreactivity of all the antibodies is found within the same structures, in small subset of cells and fibers.…”
Section: Discussionmentioning
confidence: 98%
“…In general, the markers fall into two large categories; the first being those antibodies that recognize what are supposed to be the echinoderm homologs of the antigens recognized by the antibodies in other animal species. Here we find antibodies to neurotransmitters such as serotonin (Murabe et al 2008), GABA (Newman and Thorndyke 1994) and histamine (Hoekstra et al 2012) or to their synthesizing enzymes, such as tyrosine hydroxylase (Diaz-Balzac et al 2010). Other antibodies recognize echinoderm peptides (Diaz-Miranda et al 1995), or proteins associated with the nervous system such as synaptotagmin (Burke et al 2006), calbindin (Diaz-Balzac et al 2012) or β-tubulin (Diaz-Balzac et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The nerve ring and the outer parts of the nerve cord belong to the ectonerual compartment, whereas the inner layer of the nerve cords is the hyponeural system. These two systems were thought to be separate; however, fine-structural studies and histochemistry of neurotransmitters in sea cucumbers have indicated that both systems are derived from ectoderm and are interconnected (Mashanov et al, 2007;Hoekstra et al, 2012). Moreover, Echinoderms also have numerous ectodermal sensory cells.…”
Section: Introductionmentioning
confidence: 99%